Identifying droplet boundaries: impacts of surface topography on droplet freezing and an investigation of the impacts of surfactant on sprayed droplet dynamics - Stallbaumer-Cyr, Emily M. (Kansas State University, 2023)
The formation and behavior of droplets is critical in many applications, including freezing [1-8], irrigation [9-11], heat transfer [12-14], spread of disease via respiratory droplets [15, 16], and precipitation [6, 17]. There are two research foci of this dissertation: 1) condensing droplets subsequently freezing on surfaces, and 2) droplet spray dynamics from irrigation nozzles. Freezing of droplets can cause a wide variety of problems, including frosting on windshields; icing on wind turbines and airplanes; and freezing of heat pipes, thereby reducing their ability for thermal management. Droplets also form from spray break up (e.g., irrigation and pesticides), which are critical for agricultural applications and water conservation. Water scarcity (i.e., water demand is greater than water supply and water resources [18]) is increasingly becoming an issue globally; in 2016, 71% of the global population experienced water scarcity for at least 1 month/year. This research investigates the freezing mechanisms of droplets on grooved and sintered wick surfaces found in commercial heat pipes compared to a plain copper surface. The freezing times were quantified and the different propagation mechanism (ice bridging, frost halos, and cascade freezing) were explored. The surfaces were observed for one hour under a microscope, with controlled conditions (i.e., the ambient temperature was 22°C, the relative humidity was 60%, and the surface temperature was set to -5°C). Freezing occurred earliest on the plain copper surface at 6.3 minutes and took the shortest amount of time to completely freeze (i.e., 4.6 minutes); the freezing front propagated via ice bridging with little to no interruptions. The grooved surface began freezing at 12.5 minutes and took 8.3 minutes to completely freeze. The freezing front on the grooved wick propagated via ice bridging, but took longer to freeze due to each individual groove propagating independently. The sintered surface took the longest to freeze, beginning at 16.4 minutes and took 10.9 minutes to completely freeze. The sintered wick experienced propagation via ice bridging, stochastic freezing and cascade freezing; however, freezing propagation across the surface was delayed due to voids existing between the sintered particles that did not allow ice to propagate across the voids. The addition of surfactant and its effects on spray dynamics and droplet formation was investigated using fan, full cone, and bubbler nozzles with the addition of a surfactant, Surfactin, at 0.1% concentration by weight added to distilled water, decreasing the surface tension from 72.8 mN/m to 29.2 mN/m. The fan nozzles were tested and observed at 30, 45, and 60 psi (206.8, 310.3, and 413.7 kPa) and the full cone nozzle was observed at 20, 30, 45, and 60 psi (137.9, 206.8, 310.3, and 413.7 kPa). Both fan and full cone nozzles experienced second wind induced breakup of the liquid sheets exiting the nozzle; the addition of surfactant resulted in an increased breakup length and a decreased droplet size. The fan nozzle’s volumetric median droplet diameter, D[subscript V50], decreased with the addition of surfactant (e.g., the F1 nozzle decreased by 65.6 µm, 53 µm, and 26.3 µm at 30, 45, and 60 psi respectively). The full cone nozzle DV50 decreased initially with the addition of surfactant (27.8 µm, 14.3 µm, and 13.4 µm at 20, 30, and 45 psi, respectively), but increased the D[subscript V50] at 60 psi (24.3 µm). Sprays from 6, 10, and 15 psi bubbler nozzles were measured and observed to experience Rayleigh and first wind induced breakup. The addition of surfactant increased the diameter of the jet or ligament formed from the bubbler plate, thereby increasing the breakup length and the droplet size at 10 and 15 psi (droplet size decreased by 750.6 µm and 4462.7 µm, respectively). The effect of the surfactant on was not as significant for the 6 psi bubbler nozzle. The changes in droplet sizes have implications for drift (i.e., smaller droplets are more prone to drift), coverage, and infiltration of the sprayed fluid into the soil.
Keywords: Droplets; Freezing; Surfactant; Spray breakup; Droplet size